Influence of practice location on prescribing, diabetes care, and colorectal cancer screening among Czech general practitioners during the COVID-19 pandemic - Bělobrádek, Jan; Šídlo, Luděk; Philipp, Tom (Epidemiology and health, 2024)
OBJECTIVES: The provision of primary health care was not interrupted during the coronavirus disease 2019 (COVID-19) pandemic in Czechia, although the capacity and resources of providers changed. We examined how the pandemic affected individual general practices throughout 2017-2021, focusing on differences between urban and rural practices. METHODS: We analysed data from the largest health insurance company in Czechia, which provides care to 4.5 million people (60% of the population). We evaluated the prescription volume, diabetes care procedures, and faecal immunochemical test (FIT) in preventive care and new pandemic-related procedures (remote consultations, testing, and vaccinations). For the spatial distribution of practices, we adapted the Organisation for Economic Cooperation and Development typology. RESULTS: We observed minimal declines in 2020 in the rate of prescribing (-1.0%) and diabetes care (-5.1%), with a rapid resumption in 2021, but a substantial decline in FIT (-17.8% in 2020) with slow resumption. Remote consultations were used by 94% of all practices regardless of location, with testing and vaccinations more commonly performed by rural general practitioners (GPs). CONCLUSIONS: Primary care in Czechia rose to the challenge of the COVID-19 pandemic, as shown by the finding that the volume of healthcare services provided through primary care did not decrease across most of the monitored parameters. This study also confirmed that rural GPs provide more care in-house, both in terms of prescribing and procedures performed in their practices. Future studies will need to focus on preventive care, which the pandemic has dampened in GP practices in Czechia.
Keywords: General Practitioners; Early Detection of Cancer; Diabetes mellitus; Pandemics; kolorektální nádory; diabetes mellitus; Česká republika; Middle Aged; Colorectal Neoplasms; mužské pohlaví; Diabetes Mellitus; COVID-19; Czech Republic; praktičtí lékaři; odborná praxe - umístění; časná detekce nádoru; Primary health care; primární zdravotní péče; ženské pohlaví; Humans; Practice Patterns, Physicians'; Prescriptions; lidé středního věku; pandemie; Female; Rural health; Primary Health Care; Cancer screening tests; lékařská praxe - způsoby provádění; lidé; Male; Professional Practice Location